Si alloy/graphite coating design as anode for Li-ion batteries with high volumetric energy density. (10th November 2017) - Du, Zhijia; Li, Jianlin; Daniel, C.; Wood, D.L.
Abstract: A simplified mathematical model is developed for designing high-energy-density Si alloy/graphite coatings. The design is discussed based on a set of metrics related to their implementation in practical cells including volumetric capacity, average voltage, volumetric energy density, particle expansion, and cell expansion. To achieve the same energy density improvement, one can use either high capacity Si alloys at a lower weight ratio in Si alloy/graphite coatings or low capacity Si alloys at a higher weight ratio. However, high capacity Si alloys have high volume expansion at the particle level, which tends to have SEI stabilization issues, while low capacity Si alloys lead to high volume expansion at cell level. Gravimetric energy density is also calculated in the model, and it is found that the energy density improvement based on a gravimetric basis is smaller than that of a volumetric one. The findings from this model are highly beneficial for Si alloy/graphite coating design for achieving maximum energy density with respect to the volume expansion issue.